2000
DOI: 10.1080/08927014.2000.9522793
|View full text |Cite
|
Sign up to set email alerts
|

Female strategies of harassment reduction in southern elephant seals

Abstract: Female southern elephant seals are expected to adopt behaviours that reduce the costs of male harassment. We studied the strategies and tactics of harassment reduction in two populations, at Punta Delgada (Valdés Peninsula, Argentina) and at Sea Lion Island (Falkland Islands) during five breeding seasons in all. Females synchronized their breeding activities to reduce harassment risk, and rarely bred alone to reduce the likelihood of encounters with subadult males. Females showed a clear preference for larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…2000) and other animals (e.g., Magurran and Seghers 1994;Byrne and Roberts 2000;Galimberti et al 2000;Shine et al 2000) than was previously thought.…”
Section: The Evolutionary Covariance Of Behaviors Within a Shared Matmentioning
confidence: 92%
See 1 more Smart Citation
“…2000) and other animals (e.g., Magurran and Seghers 1994;Byrne and Roberts 2000;Galimberti et al 2000;Shine et al 2000) than was previously thought.…”
Section: The Evolutionary Covariance Of Behaviors Within a Shared Matmentioning
confidence: 92%
“…Thus, this simple conflict between the sexes over mating in Gerris might constrain their key mating behaviors and associated morphologies to a limited number of evolutionary pathways. Similar conflicts over mating appear characteristic of other water strider genera (e.g., Aquarius, Sih and Krupa 1992;Weigensberg and Fairbairn 1994;Lauer 1996), as well as many other taxa (e.g., Magurran and Seghers 1994;CluttonBrock and Parker 1995;Rehfeldt 1996;Clutton-Brock and Langley 1997;Byrne and Roberts 2000;Crean et al 2000;Galimberti et al 2000;Shine et al 2000), and may similarly constrain mating-system evolution to a relatively small number of trajectories. Only comparative studies of clades, for which experimental studies have elucidated the dynamics of the conflict over mating, can address this proposition.…”
Section: The Evolutionary Covariance Of Behaviors Within a Shared Matmentioning
confidence: 99%
“…In mammals, male coercion has been described as promoting female group formation. In southern elephant seals Mirounga leonina, Galimberti et al (2000) found that females showed a clear preference for larger harems that guaranteed a reduced harassment risk. Red deer Cervus elaphus in Doñana National Park (Spain) distribute themselves in accordance with food dispersion (Carranza & Valencia 1999).…”
Section: Sexual Coercion and Females' Responsesmentioning
confidence: 95%
“…It is during these periods ashore that elephant seals are potentially vulnerable to disturbance. Human disturbance may affect a population by: (i) disrupting suckling and the transfer of resources between mother and offspring resulting in lighter weaning mass (Bryden, 1968) and increased mortality (McMahon, Burton & Bester, 2000); (ii) males trampling pups during charges at human intruders (Galimberti, Boitani & Marzetti, 2000b); and (iii) increasing the occurrence of mother–pup separations (Galimberti, Boitani & Marzetti, 2000a). However, no evidence exists for behavioural, physiological or morphometric differences between disturbed and undisturbed seals (Engelhard et al ., 2001, 2002a,b).…”
Section: Possible Reasons For Population Changementioning
confidence: 99%